A panel data analysis of temporary and permanent effects of fixed broadband penetration over economic growth - José Alberto Candelaria (International Telecommunications Society (ITS), 2015)
This article presents an econometric analysis for the effects of fixed broadband penetration on the growth rate of GDP per capita for a panel of 35 developed and developing countries over an annual period of 33 years (1981 - 2013). The article contributes to the telecommunications literature by distinguishing between temporary and permanent impacts of fixed broadband penetration on economic growth. Our methodology consists of two models, the first one is a fixed effects panel data model which is used as a benchmark, and it controls for contemporaneous and one-period lagged effects of the penetration variable on economic growth. The possibility of an endogeneity issue due to reverse causality is addressed by considering a two-stage instrumental variables (IV) fixed effects model. In a first stage we instrument the fixed broadband penetration variable with fixed telephony subscribers and the internet users for every 100 inhabitants. Then, in a second stage we use the generated fitted values in a panel regression to determine the impact over the growth rate of GDP per capita. Our approach includes as an explanatory variable the Standard and Poor's 500 real index to control for the business cycle of the global economy. Finally, we verify the existence of positive and statistically significant temporal and permanent effects of fixed broadband penetration variable over economic growth.
Keywords: C23; C26; O47; 330; Fixed Broadband Penetration; Economic Growth; Panel Data Fixed Effects; Instrumental Variables; Temporal and Permanent Effects